2018
DOI: 10.1186/s13287-018-0965-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation of MSX1 in oligodontia inhibits odontogenesis of dental pulp stem cells via the ERK pathway

Abstract: BackgroundTooth agenesis, one of the most common developmental anomalies, can affect the function and esthetics of patients. The aim of the present study was to identify genetic clues for familial tooth agenesis and explore the underlying mechanisms, focusing on the role of human dental pulp stem cells (hDPSCs).MethodsWe applied Sanger sequencing to identify the cause of oligodontia in a Chinese family. DNA transfection and functional analysis in DPSCs was also performed to explore the impact of the identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…It was recently found that Msx1 plays an important role in human odontogenesis. Specifically, a frame-shift mutation in Msx1 in human dental pulp stem cells weakened the activity of the MAPK signaling pathway and decreased the proliferation of cells, leading to the developmental deficiency of teeth ( 73 ). This mutation disrupted the Msx1 protein at the amino acid residue Met43; therefore, Ser136 was also disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently found that Msx1 plays an important role in human odontogenesis. Specifically, a frame-shift mutation in Msx1 in human dental pulp stem cells weakened the activity of the MAPK signaling pathway and decreased the proliferation of cells, leading to the developmental deficiency of teeth ( 73 ). This mutation disrupted the Msx1 protein at the amino acid residue Met43; therefore, Ser136 was also disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the homeodomain is important for the successful interaction of MSX1 with other proteins such as TATA box binding protein (TBP) and distal-less homeobox (DLX) [37,38]. However, the role of MSX1 in human craniofacial and dental development has not been fully elucidated [39].…”
Section: Discussionmentioning
confidence: 99%
“…Protocols used to acquire human tissues were previously described (Xin et al 2018) and conducted upon obtaining approval from the Ethical Guidelines of Peking University and informed consent from participants (PKUSSIRB-201311103). DPSCs were dissected from the extracted premolars of healthy donors and cultured with alpha modification of Eagle’s medium (containing 15% fetal bovine serum) at 37 °C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…DPSCs were dissected from the extracted premolars of healthy donors and cultured with alpha modification of Eagle’s medium (containing 15% fetal bovine serum) at 37 °C with 5% CO 2 . DPSCs were identified according to a previously described method (Xin et al 2018), and cells with 3 passages were used.…”
Section: Methodsmentioning
confidence: 99%